DIGITAL LANGUAGE LEARNING THROUGH DUOLINGO:: A SURVEY STUDY OF TENTH-GRADERS - Reni Oktariani; Jenny Elvinna Manurung; Nita Ria; Gaya Tridinanti (Didascein : Journal of English Education, 2025)
The rapid development of technology, particularly in the post-COVID era, has significantly expanded individuals’ perspectives, especially in the realm of education. Technology has enabled greater access to information, and numerous advanced applications are now available to specifically support the improvement of language skills. The Duolingo application is one of the technological tools that can help students become more proficient in English, and it also supports educators by offering ways to uphold the idea of technology-assisted language learning. This study aimed to investigate students’ perceptions of using Duolingo. The population of this study consisted of tenth-grade students at SMA Swasta Sukajadi during the 2023/2024 academic year. The research sample consisted of 106 students, representing classes XA, XB, and XC at SMA Swasta Sandika Sukajadi. The research findings present the results of a descriptive analysis of students' perceptions. Five aspects of students' perceptions regarding the use of the Duolingo application in English learning. The data were collected using a questionnaire. The students’ perceptions were divided into two major categories: positive and negative perceptions. Based on the findings, it can be concluded that the use of the Duolingo application significantly enhances the effectiveness and utility of English language learning. Most students demonstrated a higher level of interest in engaging with English learning through the Duolingo application